Application of imaging visibility to measurement of correlation coefficient of scattering potential - Liu, Hong; Wang, Weisheng; Liu, Jingao; Liu, Weidong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
It is shown that the imaging visibility of intensity correlated scattered field may be utilized to determine the normalized correlation coefficient of the scattering potential (CCSP) of the quasi-homogeneous (QH) media illuminated by a scalar plane wave. The relationship between the imaging visibility and the CCSP is constructed by analytical forms. As long as the visibility of the intensity correlated scattered field is known, the scaled width of the CCSP can be expressed by solutions of the inverse scattering problem.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 557-565
Keywords: optyka; scattering theory; scattering measurements